Multi-frequency HF radar measurements of artificial F-region field-aligned irregularities. - Rietveld, Michael T.; Senior, A.; Borisov, N.D.; Kosch, M.J.; Yeoman, T.K.; Honary, F. (European Geosciences Union, 2004)
We present radar backscatter power measurements using the CUTLASS HF radar at Hankasalmi, Finland from F-region field-aligned irregularities induced by HF radio pumping with the EISCAT Heating facility. A novel radar operating mode is used in which the radar frequency is rapidly swept through a number of bands, making use of the varying ionospheric refraction to probe different heights within the heated region. We obtain height profiles of backscatter power which correspond to e-folding scale lengths of around 20km for the mean-square electron density perturbations for pump wave interaction heights in the region of 240-250km in daytime conditions. The results are in agreement with previous measurements made by other techniques. We discuss some problems with the method and suggest improvements for future experiments.